2010
DOI: 10.1042/bc20090070
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 (STAT3) regulates adipocyte differentiation via peroxisome‐proliferator‐activated receptor γ (PPARγ)

Abstract: Background information. STAT3 (signal transducer and activator of transcription 3) is an important transcription factor involved in many biological events, including apoptosis, tumorigenesis, angiogenesis and epithelial-tomesenchymal transition. However, no direct evidence for a role of STAT3 in 3T3-L1 adipocyte differentiation has been reported.Results. In the present study, we found that rapid activation of STAT3, lasting for more than 48 h, was elicited upon induction of adipogenesis. Both the STAT3-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 49 publications
(61 reference statements)
2
63
1
Order By: Relevance
“…It is worth mentioning that BBR is known to regulate glucose handling and lipid metabolism in hepatocytes and adipocytes (36,40,41). Given that STAT3 is a key transcription factor in these processes (42,43) and our novel findings of BBR regulation of STAT3, it raises the possibility that BBR regulates metabolism through the JAK/STAT3 cascade, which may provide new therapeutic avenues to regulate glucose and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that BBR is known to regulate glucose handling and lipid metabolism in hepatocytes and adipocytes (36,40,41). Given that STAT3 is a key transcription factor in these processes (42,43) and our novel findings of BBR regulation of STAT3, it raises the possibility that BBR regulates metabolism through the JAK/STAT3 cascade, which may provide new therapeutic avenues to regulate glucose and lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…S1D). The Jak family of kinases have been implicated in the differentiation of white preadipocyte cell lines, particularly in the induction of the master regulators Cebpb/Cebpd and Pparg (15,16,47). Beyond this, only limited information is available on the downstream target genes in this context (14).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is known to express in human adipocytes (Harp et al 2001), mouse adipocytes (Deng et al 2006), and mouse 3T3-L1 cells (Stephens et al 1996, Wang et al 2010 to regulate adipogenesis. Activation of STAT3 activity leads to the induction of adipogenesis (Stephens et al 1996, Harp et al 2001, Wang et al 2010) and inhibition of STAT3 activity by inhibitors or siRNA resulted in suppression of adipocyte differentiation (Deng et al 2006, Wang et al 2010. In line with these findings, we found that S3I-201 treated HFDThrb PV/PV Pten C/K mice markedly decreased adipocyte cell size (Fig.…”
Section: Discussionmentioning
confidence: 99%